Autoimmune Cytopenias and Dysregulated Immunophenotype Act as Warning Signs of Inborn Errors of Immunity: Results From a Prospective Study - Schiavo, Ebe; Martini, Beatrice; Attardi, Enrico; Consonni, Filippo; Ciullini Mannurita, Sara; Coniglio, Maria Luisa; Tellini, Marco; Chiocca, Elena; Fotzi, Ilaria; Luti, Laura; D’Alba, Irene; Veltroni, Marinella; et al. (Frontiers in Immunology, 2022)
Inborn errors of immunity (IEI) are genetic disorders characterized by a wide spectrum of clinical manifestations, ranging from increased susceptibility to infections to significant immune dysregulation. Among these, primary immune regulatory disorders (PIRDs) are mainly presenting with autoimmune manifestations, and autoimmune cytopenias (AICs) can be the first clinical sign. Significantly, AICs in patients with IEI often failed to respond to first-line therapy. In pediatric patients, the tight link between autoimmune cytopenias and immune dysregulation reveals as specific immunological abnormalities can be red flags for an associated IEI. However, for these cases precise indications or parameters useful to suspect and screen for a hidden congenital immune defect are lacking. Therefore, we focused on chronic/refractory AIC patients to perform an extensive clinical evaluation and multiparametric flow cytometry analysis to select patients with a strong suspicion of PIRD as candidate for genetic analysis. Key IEI-associated alterations causative of STAT3 GOF disease, IKAROS haploinsufficiency, activated PI3Kd syndrome (APDS), Kabuki syndrome and autoimmune lymphoproliferative syndrome (ALPS) were identified. In this scenario, a dysregulated immunophenotype would act as a potential screening tool for an early IEI diagnosis, pivotal for an appropriate clinical management and for the identification of new therapeutic targets.